Identification of new heterocyclic compounds synthesized from 4-aminopyridine and evaluation their antibacterial effect (World Journal of Experimental Biosciences, 2016)
Diazotization of pyridine-4-amine (1) to form diazonium chloride salt (2): pyridine-4-diazonium chloride which undergo coupling reaction with various anions in DMF, and EtOH to give: 2-(pyridine-4-yldiazonium) isoindoline-1,3-dione (3), 2-(pyridine-4-yldiazonium) isoindoline-1-one-3-sulphoxide (4), and ethyl 2-(pyridine-4-yldiazonium) acetate (5). The last ester was converted to the acid hydrazide: 2-(pyridine-4-yldiazonium) acetohydrazide (6) which was condensed with 4-chlorobenzaldehyde in absolute ethanol and some drops of glacial acetic acid to give the Schiff’s base: N -_(4-chlorobenzylidene) -2-(pyridine-4-yldiazonium) acetohydrazide (7). Schiff’s base was reacted with benzoic acid derivatives (2-aminobenzoic acid, 2-hydroxybenzoic acid, and 2-mercaptobenzoic acid) in ethanol to give: N-[2-(4-chlorophenyl)-4-oxo-1,2-dihydroquinazoline-3-(4H)-yl]-2-(pyridine-4-yldiazonium)acetamide (8), N-[2-(4-chloro-phenyl)-4-oxo-2Hbenzo[e][1,3]oxazine-3-(4H)-yl-2- (pyridine-4-yldi azonium)acetamide (9), and N-[2-(4-chlorophenyl)-4-oxo-2H-benzo[e][1,3]thiazine-3-(4H)-yl]-2-(pyridine-4-yldiazonium)acetamide (10). The spectral methods of the prepared compounds were characterized by FT.IR, 1HNMR (for compounds (4, and 10), and Uv-Vis (for compounds (3,4,8,9, and 10), besides melting points were recorded and the purity was checked through T.L.C. technique. Antibacterial activity for some of the synthesized compounds was screened.